Increase in Vitamin D but not Regulatory T Cells following Ultraviolet B Phototherapy of Patients with Atopic Dermatitis - Stine Simonsen; Charlotte M. Bonefeld; Jacob P. Thyssen; Carsten Geisler; Lone Skov (Medical Journals Sweden, 2018)
This study investigated serum 25-hydroxyvitamin D (25(OH)D) concentrations and circulating regulatory T cells in patients with atopic dermatitis receiving narrow-band ultraviolet B (nbUVB) phototherapy. Thirty adult patients with atopic dermatitis were included. Blood samples were collected at baseline and at weeks 2 and 4 of nbUVB phototherapy. Skin biopsies were taken at baseline and at week 4. Serum 25(OH)D concentrations increased significantly following nbUVB phototherapy (estimate of change from baseline to week 2: 32.00 nmol/l, confidence interval (CI) 20.48-43.52, p <0.0001, n = 25; and from baseline to week 4: 50.30 nmol/l, CI 37.28-63.33, p< 0.0001, n = 18). This increase was independent of the filaggrin gene FLG loss-of-function mutation status. Flow cytometry showed no significant change in regulatory T cells or cytokine profiles of T cells in blood. Real-time quantitative PCR showed no change in skin cytokine levels. In conclusion, nbUVB phototherapy was associated with increased serum 25(OH)D concentrations, but not changes in circulating regulatory T cells in patients with atopic dermatitis.